2017
DOI: 10.1128/jvi.00627-17
|View full text |Cite
|
Sign up to set email alerts
|

The SAT Protein of Porcine Parvovirus Accelerates Viral Spreading through Induction of Irreversible Endoplasmic Reticulum Stress

Abstract: The SAT protein (SATp) of porcine parvovirus (PPV) accumulates in the endoplasmic reticulum (ER), and SAT deletion induces the slow-spreading phenotype. The in vitro comparison of the wild-type Kresse strain and its SAT knockout (SAT Ϫ ) mutant revealed that prolonged cell integrity and late viral release are responsible for the slower spreading of the SAT Ϫ virus. During PPV infection, regardless of the presence or absence of SATp, the expression of downstream ER stress response proteins (Xbp1 and CHOP) was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…However, a study of vesicular stomatitis virus demonstrated that ER stress activation inhibited viral infection (Baltzis et al, 2004). Previous studies have shown that treatment with the ER stress inducer MG132 inhibited infection by PPV strain NADL-2, similar to the results observed with PPV strain Kresse infection at a low MOI (Boisvert et al, 2010;Meszaros et al, 2017). Meszaros et al also showed that the specific ER stress inducer Tg inhibited infection by PPV strain Kresse.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…However, a study of vesicular stomatitis virus demonstrated that ER stress activation inhibited viral infection (Baltzis et al, 2004). Previous studies have shown that treatment with the ER stress inducer MG132 inhibited infection by PPV strain NADL-2, similar to the results observed with PPV strain Kresse infection at a low MOI (Boisvert et al, 2010;Meszaros et al, 2017). Meszaros et al also showed that the specific ER stress inducer Tg inhibited infection by PPV strain Kresse.…”
Section: Discussionmentioning
confidence: 65%
“…The early stage of infection with the attenuated PPV NADL-2 strain was almost completely abolished by the ER inducer MG132 (Boisvert et al, 2010). A similar inhibitory effect of MG132 treatment of infection with PPV strain Kresse was detected at a low MOI (Meszaros et al, 2017). These data suggested that ER stress has both negative and positive effects on PPV replication related to the strain and dose of the virus.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations